Gravitational aeration tower filter system to increase the dissolved oxygen amount for iron removal in groundwater - Radzi, E. Z.; Wahab, Md Saidin; Sahdan, M. Z.; Hamdan, R.; Zakariah, R. A. (UTHM Publishing, 2020)
This paper discusses the Gravitational Aeration Tower Filter System (GATS) aims to increase the amount of Dissolved Oxygen (DO) for iron removal in groundwater. The groundwater is mainly used in remote areas. The presence of a large volume of iron contained in the groundwater will subject to water contamination besides limiting the lifespan of existing water filter to filter the contaminants. Pre-treatment systems i.e., aeration techniques are often used to reduce the amount of iron contained in the groundwater. One of the aeration techniques i.e., the GATS is proposed and designed for this work. The GATS is tested to assess its effectiveness in increasing the DO and in the removal of iron in the water. The study area is located in Kampung Majid Ibrahim, Simpang Renggam. The initial value of the iron in the tubewell ranged from 1.4 mg/L to 2.3 mg/L, which exceeded the standard limit of 0.3 mg/L. Using AQUAREAD AP2000 and Hanna High Iron Checker, data collection is carried out in-situ testing. The flow rate is set at 5.5 L/min through the GATS, with varying air parameters. The results of the GATS test demonstrate the DO percentage increases up to 90.50 % and the percentage of iron removal is up to 10.24% with an airflow of 1.0 L/min.